2009
DOI: 10.1097/jcp.0b013e3181a39137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Testosterone Replacement in Middle-Aged Men With Dysthymia

Abstract: Mid-life onset male dysthymic disorder (DD) seems to be a distinct clinical condition with limited therapeutic options. Testosterone replacement is mood-enhancing and has been proposed as an antidepressant therapy, though this strategy has received limited systematic study. We therefore conducted a six-week double-blind placebo-controlled clinical trial in 23 men with DD and with low or low-normal testosterone (T) level (i.e, screening total serum testosterone<350 ng/dL). Enrolled men were randomized to receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 49 publications
2
26
0
1
Order By: Relevance
“…Although a larger more recent study failed to show a difference between testosterone and placebo on behavioral measures in HIV-positive men (Rabkin et al, 2004), androgens continue to be widely used in this population. Also in the last ten years, a series of studies has investigated testosterone as a possible antidepressant treatment, administered either as a monotherapy (Perry et al, 2002; Seidman et al, 2009; Seidman et al, 2001) or as an augmentation strategy (Orengo et al, 2005; Pope et al, 2003; Seidman et al, 2005; Seidman and Rabkin, 1998). We have reviewed this literature in detail elsewhere (Kanayama et al, 2007a).…”
Section: Historymentioning
confidence: 99%
“…Although a larger more recent study failed to show a difference between testosterone and placebo on behavioral measures in HIV-positive men (Rabkin et al, 2004), androgens continue to be widely used in this population. Also in the last ten years, a series of studies has investigated testosterone as a possible antidepressant treatment, administered either as a monotherapy (Perry et al, 2002; Seidman et al, 2009; Seidman et al, 2001) or as an augmentation strategy (Orengo et al, 2005; Pope et al, 2003; Seidman et al, 2005; Seidman and Rabkin, 1998). We have reviewed this literature in detail elsewhere (Kanayama et al, 2007a).…”
Section: Historymentioning
confidence: 99%
“…A case report does not allow to make far reaching conclusions as to the mechanism but it could be that, in addition to breaking the self-sustaining vicious circle of MS-obesity hypognadal testosterone levels, the mood-elevating effects of normalizing testosterone may have played a role (22). More studies are needed to distinguish between the effects of weight loss and/or exercise on somatic and mental features associated with the MS and to test whether treatment of testosterone has an additional positive effect.…”
Section: Discussionmentioning
confidence: 99%
“…Mood-elevating effects of testosterone have been reported (22), but the loss of body weight may have had an independent positive effect on mood, though studies indicate that weight loss has a positive effect on psychological factors but improvement of depressive mood states is less clear (23). In population studies, it has been found that erectile function improves when weight declines, so the loss of weight, in this case, may have also been a factor in improvement of scores on the IIEF (24).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant to these sex-specific differences is the demonstrated sensitivity of affective disorders to steroids. Specifically, anxiety disorders and depression increase with menopause and andropause (Arpels 1996; Lund et al 1999; Cooper and Ritchie 2000; Eskelinen et al 2007), and improvement of these symptoms is reported for both sexes with hormone replacement therapy (Cooper and Ritchie, 2000; Yazici et al 2003; Genazzani et al 2004; Kumano 2007; Seidman et al 2009; Amore et al 2009). …”
Section: Aas Classes and Current Usementioning
confidence: 99%